The ifo Tax and Transfer Behavioral Microsimulation Model - Maximilian Blömer; Andreas Peichl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper describes the ifo Tax and Transfer Behavioral Microsimulation Model (ifoMSM-TTL), a policy microsimulation model for Germany. The model uses household microdata from the German Socio-Economic Panel and firm data from the German Linked Employer-Employee Dataset. This microsimulation model consists of three components: First, a static module simulates the effects of a tax-benefit reform on the budget of the individual household. This includes taxes on income and consumption, social security contributions, and public transfers. Secondly, behavioral labor supply responses are estimated. Thirdly, a demand module takes into account possible restrictions of labor demand and identifies the partial equilibrium of the labor market after the supply reactions. The demand module distinguishes our model from most other microsimulation tools.
Keywords: D58; H20; J22; J23; 330; tax and benefit systems; labor supply; labor demand; Germany; policysimulation